BASE METAL (BM) AND PLATINUM-GROUP ELEMENTS (PGE) MINERALOGY AND GEOCHEMISTRY OF THE ELMASLAR CHROMITE DEPOSIT (DENIZLI, SW TURKEY): IMPLICATIONS FOR A LOCAL BM AND PGE ENRICHMENT - Akbulut, Mehmet; Pișkin, Özkan; Arai, Shoji; Özgenç, İsmet and Minareci, Fevzi (Ofioliti, 2010)
The Elmaslar Chromite Deposit (ECD) in Denizli (SW Turkey) consists of chromitite enveloped by highly refractory replacive dunite within a depleted harzburgite. The composition of chromian spinel is Cr-rich suggesting derivation from boninitic melt-peridotite interaction beneath a supra-subduction zone. The chondrite normalized PGE patterns show predominance of Ir-group (IPGE) over Pd-group PGE (PPGE) that is consistent with ophiolitic podiform chromitites in general. The primary PGM paragenesis of ECD mainly consists of laurite-erlichmanite series with minor Pd bearing phases. Dominance of Osrich laurite over the Os-poor ones suggests initially high fS2 during crystallization of chromitite. It also indicates a slow cooling rate of the chromitite parent melt. Coexistence of irarsite with erlichmanite suggests increase in As activity during late stages of chromitite crystallization. One peculiar contact zone sample with disseminated-massive chromitite enveloped by dunite shows unusually high PPGE content and positive-sloped chondrite normalized PGE pattern. This enrichment is attributed to a two stage process: (i) primary and local sulfur saturation, (ii) followed by secondary hydrothermal alteration causing smallscale remobilization and precipitation of PGE. No mode of occurrence is suggested for the primary and local sulfur saturation stage, because there is no direct field evidence on the geological setting of the sample. However, it is clear that the effects of this event were limited and not deposit wide. The secondary enrichment of PGE is mainly attributed to introduction of fluids during serpentinization. The amphibole-pyroxene-spinel-silica-carbonate rocks found in the stockpiles of ECD are remarkable. The role of these rocks, in the secondary PGE enrichment in ECD stays to be questioned. They mark further low-temperature CO2-metasomatism in ECD and provide promising indicators for investigating secondary PGE occurrences in chromitites.